The Role of Corporate Social Responsibility, Ownership Structure, and Gender Diversity in Firm Performance - Alawi, Suha (International Journal of Economics and Financial Issues, 2024)
Corporate social responsibility (CSR) is now at the heart of corporate sustainability, and as such should have a significant impact on firm performance. However, the ownership structure (OS) is one element in the inner functioning of corporate governance (CG). Further, diversity by gender is one of the variables affecting FP. This paper examines the impact of CSR, ownership structure and gender diversity on FP. That is, we use panel data from non-financial firms in South Asian economies. Data for the years 2010-2022 are drawn from players ’DataStream. We use fixed effect, GMM (generalized method of moments) analysis and propensity score matching to study the data. However, we discover CSR and ownership concentration as well as institutional ownership and gender diversity have positive impacts on FP. study provides the policy implications for both investors and firms. As FP increases with more CSR activities, investors prefer to invest in firms that are more socially connected. Firms should provide more chances to the women on the board to improve performance. Further, ownership structure helps to overcome agency costs, therefore, investors are more attracted to provide funds to the firms that have a higher share of concentrated and institutional ownership.